Athlete's Perceptions of a “Quarantine” Training Camp During the COVID-19 Lockdown - Washif, Jad Adrian; Mohd Kassim, Siti Fuzyma Ayu; Lew, Philip Chun Foong; Chong, Christabelle Sheau Miin; James, Carl (Frontiers in Sports and Active Living, 2021)
Globally, COVID-19-related movement restrictions have caused significant disruption to athlete's training and sporting competitions. “Quarantine” camps are one approach to maintain sport-specific training, whilst minimizing the risk of COVID-19 transmission between athletes and society. This cross-sectional study investigated the effects of a “quarantine” training camp on athlete's routines and wellbeing, performance support, perceived stress and sleep behaviors. A survey was completed at the end of a 30-day “quarantine” camp, by 76 elite athletes (17–46 years), predominantly (~80%) Olympic/Paralympic and/or world championship representatives. Athletes described their experiences in comparison to; pre-lockdown training and/or training during “lockdown” (immediately prior to the “quarantine” camp). Compared to “lockdown,” the “quarantine” camp revealed improvements (p < 0.05; 0.33 ≤ d ≤ 0.90) in access to sport-specific training (28.6%), recovery facilities (22.2%), nutritional choices (17.5%), mental (12.4%) and emotional (11.4%) health, training motivation (20.0%); and perceived stress (7.4%, d = −0.27, p = 0.026). The camp resulted in a lower sleep duration (−8.5%, d = −0.73, p = 0.014), but an improved global sleep behavior score (−5.6%, d = −0.22, p = 0.001). During the camp, the performance support athletes received was not different to pre-lockdown (p > 0.05), but there was greater sports massage (20.4%, d = 0.39) and physiotherapy usage (18.1%, d = 0.36) (both p < 0.05). The adverse effects of lockdown were restored during the camp. A “quarantine” camp may offer comparable training experiences to pre-lockdown training, without inducing additional perceived stress. Coaches and sporting organizations may consider this approach as part of a virus mitigation strategy, whilst maintaining sport-specific training.